Advanced Modeling and 3D Printing Techniques for Game and CGI Characters - Ștefan-Andrei LAZĂR; Patricia Isabela BRĂILEANU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
This article explores the methods of designing 3D elements used in video games and CGI, highlighting the impact of these techniques on the perception and experience of digital art. 3D models are fundamental to create immersive virtual worlds, and the 3D modeling process extends from conception to execution, combining engineering principles with industrial design. Advanced threedimensional modeling software such as Blender or Adobe Substance 3D Painter are built to create realistic models, while additive manufacturing with SLA technology allows rapid prototype development of game characters. The article also discusses the interoperability between certain three–dimensional modeling platforms on the current market and the impact of new technologies such as the so-called digital twins or the metaverse, on the future of three-dimensional graphics and threedimensional modeling of game characters. Through these technological advances, 3D modeling is redefining the boundaries of design, offering limitless opportunities for innovation in the gaming industry.